Characterisation of adherens and tight junctional molecules in normal animal larynx; determining a suitable model for studying molecular abnormalities in human laryngopharyngeal reflux. Issue 12 (25th November 2005) - Gill, G A; Buda, A; Moorghen, M; Dettmar, P W; Pignatelli, M
Abstract : Background: The disruption of intercellular junctions in the larynx is a pathological feature of laryngopharyngeal reflux (LPR). Good experimental models are necessary to gain greater insight into the molecular mechanisms and alterations that result from abnormal exposure of the laryngeal epithelium to acid refluxate. Aims: To characterise laryngeal tissues from different species to determine the most suitable for use in experimental studies of LPR. Methods: Human and non-human laryngeal tissues (mouse, rat, guinea pig, porcine, and rabbit) were studied. Histological characterisation was performed by light microscopy. The expression and subcellular localisation of adherens junctional molecules (E-cadherin and β catenin) was evaluated by immunohistochemistry, and tight junction molecules (occludin and zonula occludens 1 (ZO-1)) by western blotting. The ultrastructural features of porcine and human tissue were assessed by electron microscopy. Results: Porcine tissue revealed both respiratory-type and stratified squamous epithelium, as seen in the human larynx. The expression and subcellular localisation of the E-cadherin–catenin complex was detected in all species except mouse and rat. The pattern of ZO-1 and occludin expression was preserved in all species. Conclusion: The expression of intercellular junctional complexes in porcine epithelium is similar to that seen in humans. These results confirm the suitability of these species to study molecular mechanisms of LPR in an experimental system.